Permasalahan di Sekitar PAUD Kota Palangka Raya: Kontribusi PAUD lintas Agama (Islam, Kristen, Hindu dan Kaharingan) - Fitriana, Fitriana; Elisabeth, Rina; Esa, Dwi Kurnia; Nopraeda, Nopraeda; Munte, Alfonso (LPPM Institut Al Azhar Menganti Gresik, 2023)
This research seeks the extent of professional development of kindergarten teachers at Al-Hudaa Kindergarten in Palangka Raya (as an Islamic kindergarten and at the same time remains inclusive), Bukit Raya Indah Kindergarten, Dharma Wanita Persatuan Kindergarten and Bakuwu Kindergarten looking at the problems in the field (lack of educators, lack of donors from the government in general, adaptation of the use of the 2013 curriculum to the independent curriculum when there are shortcomings here and there and learning models/media that are still conventional). This research method is qualitative research with interview techniques and displays narratives from research subjects. In this study, researchers found important responses from the subjects when discussing the role of teacher professionalism in the context of PAUD in Central Kalimantan, some subjects saw that professional teachers are teachers who are able to be responsible in carrying out roles and responsibilities, which are based on the principles of teacher professionalism. However, at the same time, challenges and opportunities are the responsibility of teachers - whether they are Muslim, Christian or Hindu and with other inter-professionals. The researcher conducted a qualitative research using the interview method with the principals of PAUD located in Palangka Raya City, Central Kalimantan, namely Al-Hudaa Palangka Raya Kindergarten, Bukit Raya Indah Kindergarten, Dharma Wanita Persatuan Kindergarten and Bakuwu Kindergarten.